DNI measurement and long-term prediction of its availability in the South of Portugal - Cavaco, Afonso Manuel Dias (2020)
The knowledge of Direct Normal Irradiance (DNI) availability is becoming essential nowadays for solar concentration applications, particularly for the development of Concentrated Solar Power (CSP) plants. Thus, DNI measurements and the application of reliable solar radiation data processing methodologies are required to provide the most accurate results as possible. This thesis presents the work carried out to develop and maintain a solar radiation monitoring network and discusses the results obtained to assess the long-term DNI annual availability in the South of Portugal. The work comprised the installation, calibration and continuous operation of new measuring stations, with the objective of obtaining high quality data series. Procedures for solar radiation data gathering and processing are presented and new methods to estimate the long-term DNI annual availability based on global and diffuse horizontal irradiation are proposed and discussed. The measurements obtained and the application of the developed methods allowed to estimate and map the DNI resource in the region; RESUMO: Medição de DNI e previsão a longo prazo da sua disponibilidade no sul de Portugal O conhecimento da disponibilidade média anual de Irradiância Directa Normal (DNI) está-se a tornar essencial para aplicações de concentração solar, particularmente para o desenvolvimento de centrais de concentração solar (CSP). Deste modo, é necessária a medição de radiação solar directa normal e aplicação de métodos de processamento de dados fiáveis de modo a providenciar os resultados mais precisos possíveis. Esta tese apresenta o trabalho realizado para desenvolver e manter uma rede de medição de radiação solar e discute os resultados obtidos para avaliar a disponibilidade média anual de DNI a longo prazo no sul de Portugal. O trabalho desenvolvido incluiu a instalação, calibração e operação contínua de novas estações de medição, com o objectivo de se obterem séries de dados de elevada qualidade. Procedimentos para recolha e processamento de dados de radiação solar são apresentados e novos métodos para estimar a disponibilidade anual de DNI a longo prazo, com base em irradiação solar global e difusa, são propostos e discutidos. As medições realizadas e a aplicação dos métodos desenvolvidos permitiram estimar e mapear o DNI na região.